Development of web based information system on rental house for students UiTM Campus Tapah, Perak / Izzat Aziz - Izzat, Aziz (2016)
The problem statement of this project is the student of UiTM Campus Tapah, Perak had been facing difficulty to find information about the rental house because Tapah is a small town, and the data of rental house is a low chance to get. This study aims to develop a web-based information system of the rental house that helps the students of UiTM Campus Tapah, Perak to search the data of rental house by providing some information that related to it. If the owner of rental house use this system, they can easily promote their information of rental house to the student. Furthermore, the admin of this system is staff department of Non-Resident and Resident of UiTM Campus Tapah, Perak. The administrator course this system to manipulate the data student of Non-Resident of UiTM Campus Tapah, Perak and easily to identify of personal information of owner. The waterfall development module has been used as a guideline methodology for this system. The main software has been used is Notepad++ in the production of the system interface and all the codes. Additional software such as Adobe Photoshop CS6 is used in designing and editing. For the database, MySQL has been used the phpMyAdmin as database and communicate using a web server. The results measured of the acceptance by feedback from the survey is 65 percent of them was interested this system and 35 percent of them a not interested this system. The future work hope that this system will be improved and add more function into this system to make more functionality system. It is hoped that this system will be useful for the students of UiTM Campus Tapah, owner of the rental house, and the staff department of Non-Residents and Residents UiTM Campus Tapah.